A microprocessor stance and swing control orthosis improves balance, risk of falling, mobility, function, and quality of life of individuals dependent on a knee-ankle-foot orthosis for ambulation - Ruetz, Axel; DiBello, Tom; Toelle, Chris; Hemmen, Bea; Wening, Jason; Weber, Eric; Braatz, Frank; Winkler, Tobias; Steinfeldt, Friedemann; Umari, Marina; Rupp, Rüdiger; Kluge, Sascha; et al. (Disability and rehabilitation, 2023)
When prescribing traditional knee-ankle-foot orthoses (KAFOs), their known limitations, such as limited function and mobility, and the requirement to walk with compensatory mechanisms, especially on non-level terrains, should be considered.For patients with compromised balance and increased risk of falling when using a traditional KAFO, a microprocessor stance and swing control orthosis (MP-SSCO) may be considered as an orthotic option to reduce their fall risk.For patients with mobility restrictions using a traditional KAFO, a MP-SSCO may be considered to improve function, mobility, reintegration into normal living, and quality of life.
Online veröffentlicht: 26. September 2023
Gesehen am 05.12.2023